Hydrochromic flexible intelligent film and preparation method thereof
By mixing the polymer precursor with hydrophilic modified mesoporous nano-microspheres and performing hydrophilic treatment, a water-discolored flexible intelligent film that can respond under different humidity conditions was prepared, solving the problem of insufficient functionality of existing materials. , realizes efficient optical modulation and stability, and is suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202411650936.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-01-14
AI Technical Summary
Existing single flexible materials cannot effectively respond to complex and changeable environmental changes, cannot achieve self-regulation in actual application scenarios, and their functionality is not enough to meet multiple application needs.
By mixing the polymer precursor with hydrophilic modified mesoporous nano microspheres, curing it into a film, and hydrophilic treatment in aqueous polyethyleneimine solution, a different optical properties can be prepared that can exhibit different humidity conditions. Water-induced discoloration flexible intelligent film uses the change in water absorption refractive index of microspheres to achieve humidity response.
The preparation of different films in dry and humid environments is achieved, with the highest light transmittance up to 70%, the lowest light transmittance up to 9%, the maximum optical modulation range reaches 60%, and the maximum optical modulation range is maintained after bending, stretching and repeated discoloration cycles. Good optical stability and color distortion ability, suitable for a variety of application scenarios.
Smart Images

Figure CN119306983A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of stimulus-responsive flexible smart materials, and specifically relates to a method for preparing a hydrochromic flexible smart film based on a flexible polymer and a hydrophilic mesoporous microsphere composite material. Background Art
[0002] Humidity-sensitive materials can achieve the effect of hydrochromicity by responding to changes in humidity in the environment, thereby realizing the regulation of the visible light band. The hydrochromic film prepared based on this principle is energy-free, pollution-free, green and environmentally friendly, and can be applied to a variety of application scenarios. It has good prospects in the fields of smart windows, building materials, greenhouses, etc. Polymers such as PDMS and PI have excellent stretchability and bendability, high transmittance in the visible light band, corrosion resistance, good thermal stability and non-toxicity, and are good flexible materials. However, the functionality of a single material is insufficient, and in the face of complex and changeable actual application scenarios, it cannot respond to stimulating environmental changes. The development of smart materials that can self-regulate according to environmental changes is a future development trend. Summary of the invention
[0003] The purpose of the present invention is to prepare a stimuli-responsive hydrochromic flexible smart film based on polymer@mesoporous microspheres. The present invention can prepare a film with high haze in a dry environment and low haze in a humid environment, as well as a film with low haze in a dry environment and high haze in a humid environment according to different actual application environment requirements; at the same time, different light transmittances can be obtained by different proportions of microspheres and controlling the thickness of the film, with the highest being 70% and the lowest being 9%, and the maximum optical modulation range reaching 60%.
[0004] To achieve the above object, the present invention provides the following technical solutions.
[0005] A method for preparing a hydrochromic flexible smart film comprises the following steps: mixing a polymer precursor with hydrophilically modified mesoporous nanospheres, and then curing the mixture into a film to obtain a hydrochromic flexible smart film. Preferably, after curing the film, the obtained film is hydrophilically treated to obtain a hydrochromic flexible smart film.
[0006] Further preferably, the hydrophilic treatment comprises the following steps: immersing the film in a polyethyleneimine (PEI) aqueous solution to complete the hydrophilic treatment.
[0007] In the present invention, the hydrophilic modification is a hydrophilic group or a hydrophilic polymer modification. Preferably, the hydrophilic modification includes one or more modifications of hydroxyl, secondary amino, polyoxyethylene methacrylate, and polyethylene glycol.
[0008] In the present invention, the mesoporous nanospheres include one or more of silicon dioxide microspheres and titanium dioxide microspheres. Preferably, the mesoporous nanospheres are polydisperse mesoporous nanospheres or monodisperse mesoporous nanospheres.
[0009] The invention discloses a method for preparing a hydrochromic flexible intelligent film, comprising the following steps: (1) Synthesis of mesoporous nanospheres; (2) hydrophilically modifying the mesoporous nanospheres obtained in step (1); (3) mixing the polymer precursor and the hydrophilically modified mesoporous nanospheres prepared in step (2) in a certain proportion, and then curing the mixture to prepare a hydrochromic smart film; (4) The hydrochromic smart film obtained in step (3) is immersed in a PEI aqueous solution for hydrophilic treatment to obtain a hydrochromic flexible smart film, thereby improving the humidity responsiveness of the film.
[0010] In the present invention, the preparation process of the hydrochromic flexible smart film includes but is not limited to spin coating, scraping, printing, and spraying processes, and the thickness can be adjusted in the range of 20 μm to 1 mm or even more than 1 mm. The hydrochromic flexible smart film is prepared by uniformly mixing a polymer and mesoporous nano-microspheres and then curing them, and comprises two components: a polymer (including but not limited to flexible polymers such as polydimethylsiloxane (PDMS), polyethylene terephthalate (PET), and polyimide (PI)) and mesoporous nano-microspheres (including but not limited to silicon dioxide (SiO2), titanium dioxide (TiO2), etc.). Furthermore, the flexible film is treated with PEI hydrophilicity and has good responsiveness to humidity.
[0011] In the present invention, the mesoporous nanospheres are modified by hydrophilic groups or hydrophilic polymers, and the hydrophilic modifications include but are not limited to hydroxyl groups, secondary amino groups, polyoxyethylene methacrylate, polyethylene glycol and the like.
[0012] The humidity-sensitive flexible smart film prepared by the present invention exhibits different optical properties under different humidity conditions, including but not limited to transmittance, haze and color; and the hydrochromic film prepared using mesoporous nano-microspheres of different sizes has different optical responses. Among them, the response of the hydrochromic film prepared using polydisperse mesoporous nano-microspheres to humidity is manifested as changes in transmittance and haze; the response of the hydrochromic film prepared using monodisperse mesoporous nano-microspheres to humidity includes changes in absorption peaks in addition to changes in transmittance and haze, which is manifested as a color appearance changing into a colorless appearance.
[0013] As an example, the present invention discloses a hydrochromic flexible smart film, including a polymer film and hydroxyl-modified mesoporous SiO2 microspheres therein.
[0014] The invention discloses a method for preparing the hydrochromic flexible intelligent film, which comprises mixing hydroxyl-modified mesoporous SiO2 microspheres and a polymer precursor, forming a film, and then subjecting the mixture to a hydrophilic treatment to obtain the hydrochromic flexible intelligent film.
[0015] In the present invention, the particle size of the mesoporous SiO2 microspheres is 10 to 500 nm, preferably, the particle size of the mesoporous SiO2 microspheres is 40 to 300 nm; as an example, CTAB (hexadecyltrimethylammonium bromide) and TEOS (tetraethoxysilane) are used as raw materials to prepare polydisperse / monodisperse mesoporous SiO2 microspheres, which are then calcined to obtain mesoporous SiO2 microspheres.
[0016] In the present invention, alkali is used to modify the mesoporous SiO2 microspheres to obtain hydroxyl-modified mesoporous SiO2 microspheres.
[0017] In the present invention, the polymer precursor includes a polymer solution, a raw material for preparing a polymer, etc., which is mixed with hydroxyl-modified mesoporous SiO2 microspheres and formed into a film using a conventional method.
[0018] In the present invention, the hydrophilic treatment comprises the following steps: soaking the membrane in a PEI aqueous solution to complete the hydrophilic treatment.
[0019] In the present invention, the mass ratio of hydroxyl-modified mesoporous SiO2 microspheres to polymer film precursor is 1: (1-9).
[0020] The present invention discloses the use of the hydrochromic flexible intelligent film in the preparation of or as a humidity responsive material, or in the preparation of or as an optical responsive material, or in the preparation of or as a transmittance, haze or appearance responsive change material.
[0021] Compared with the prior art, the advantages of the present invention are: (1) The present invention combines PDMS polymer with hydroxyl-modified mesoporous SiO2 microspheres, and can obtain a humidity-sensitive smart film with controllable thickness and adjustable optical properties through processes such as spin coating, scraping, spraying, and printing. PDMS provides the film with good bendability, stretchability, corrosion resistance, and thermal stability. The property of the hydroxyl-modified mesoporous SiO2 microspheres changing their refractive index when absorbing water enables the film to respond to changes in humidity and produce changes in optical properties.
[0022] (2) The present invention can prepare films with high haze in dry environments and low haze in humid environments, as well as films with low haze in dry environments and high haze in humid environments, according to different actual application environment requirements. At the same time, different light transmittances can be obtained by varying the proportion of SiO2 microspheres and controlling the thickness of the film. The highest transmittance can reach 70%, the lowest can reach 9%, and the maximum optical modulation range can reach 60%.
[0023] (3) The present invention can maintain good optical stability and color change ability after bending, stretching, and repeated color change cycles. After 5000 cycles, the transmittance modulation range can be maintained above 95%.
[0024] (4) The process used in the present invention is simple, low-cost, and can be industrially mass-produced. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Actual photos of the smart flexible film before and after water absorption provided by some embodiments of the present invention, wherein a and b are photos of the dry and water-absorbing states of the film obtained in Example 1; c and d are photos of the dry and water-absorbing states of the film obtained in Example 2; e and f are photos of the dry and water-absorbing states of the film obtained in Example 3; g and h are photos of the dry and water-absorbing states of the film obtained in Example 5.
[0026] Figure 2 The transmittance and haze of Example 1 of the present invention before and after water absorption.
[0027] Figure 3 The transmittance and haze of Example 2 of the present invention before and after water absorption.
[0028] Figure 4 The transmittance and haze of Example 3 of the present invention before and after water absorption.
[0029] Figure 5 Scanning electron microscope images of some SiO2 microspheres synthesized in the present invention, wherein a is the 40-70 nm SiO2 microspheres synthesized in Example 1; b is the polydisperse SiO2 microspheres synthesized in Example 2; and c is the SiO2 microspheres with D50=220 nm synthesized in Example 3.
[0030] Figure 6 The particle size distribution of SiO2 is D50=220 nm.
[0031] Figure 7 This is the transmittance and haze of Comparative Example 1 of the present invention before and after water absorption.
[0032] Figure 8 The transmittance and haze spectra of Example 4 of the present invention (without PEI immersion) before and after water absorption.
[0033] Fig. 9 The time-resolved transmittance spectra of Example 1 and Example 4 of the present invention at 600 nm.
[0034] Fig.10 The transmittance and haze spectra of Example 5 of the present invention before and after water absorption. DETAILED DESCRIPTION
[0035] The present invention combines a polymer with modified mesoporous microspheres to prepare a composite material, which is an effective strategy for realizing a hydrochromic smart flexible film. The PDMS polymer is combined with hydroxyl-modified mesoporous SiO2 microspheres, which will produce a change in the refractive index after absorbing water, so that the spectrum of the composite material of the polymer and the microspheres will also change accordingly with changes in humidity.
[0036] The hydrochromic flexible smart film prepared by the present invention is a hydrochromic polymer @ mesoporous microsphere film. Taking PDMS and hydroxyl-modified mesoporous silica microspheres as an example, SiO2 microspheres are dispersed in PDMS. The size and proportion of SiO2 microspheres determine the transmittance of the PDMS@SiO2 film and its optical properties that change with humidity.
[0037] The preparation method of the hydrochromic flexible smart film comprises the following steps: (1) Synthesis of mesoporous SiO2 microspheres by improved Stöber method: 0.26-0.38 g CTAB, 23.2-26.1 ml ethanol, 3-9 ml H2O and 0.5-1 ml ammonia were mixed in sequence, and then a mixed solution of 1.5-2.2 ml TEOS and 23.2-26.1 ml ethanol was added. The mixture was stirred at 500-1500 rpm for 2-12 h to obtain 40-300 nm polydisperse / monodisperse mesoporous SiO2 microspheres. (2) The obtained polydisperse / monodisperse mesoporous SiO2 microspheres are filtered, washed with water and dried in an oven; then calcined in a muffle furnace to remove the CTAB template, thereby obtaining mesoporous SiO2 microspheres; (3) Mixing the mesoporous SiO2 microspheres with a NaOH solution and reacting them in a water bath for 1 to 3 hours to modify the surface hydroxyl groups; then washing with water to obtain water-dispersed hydroxyl-modified mesoporous SiO2 microspheres; (4) The obtained hydroxyl-modified mesoporous SiO2 microspheres are centrifuged and added to the PDMS preparation raw materials at a ratio of 10-50 wt%, and stirred to mix evenly; then coated on a clean glass substrate, cured on a heating table, and peeled off after natural cooling; (5) The obtained film is immersed in a PEI aqueous solution for 30 to 60 minutes for hydrophilic treatment to obtain a hydrochromic PDMS@SiO2 film, which is a hydrochromic flexible smart film.
[0038] Water absorption experiment: Place the dry film in an environment with 80% humidity to allow the film to fully absorb water (for 5 min), and the appearance of the film will change.
[0039] The following is a detailed description of the technical progress of the present invention through specific experiments. The raw materials used are existing products, and the specific preparation operations and performance tests are conventional techniques. The PDMS main agent and curing agent were purchased from Dow Corning; the polyethyleneimine molecular weight is 600Da, which was purchased from Aladdin, and 0.8 g PEI was dissolved in 100 mL to prepare a PEI aqueous solution. All the full transmittance spectra and parallel transmittance spectra involved were measured using a UV-Vis-NIR spectrometer. The glass substrate was ultrasonically cleaned with Decon diluent, anhydrous ethanol and isopropanol in turn, and a clean glass substrate was obtained after drying. Embodiment 1
[0040] (1) Synthesis of SiO2 microspheres by improved Stöber method: 0.38 g CTAB, 23.2 ml ethanol, 3 ml water and 0.8 ml ammonia water (28 wt%) were mixed evenly to obtain solution A; a mixed solution of 2.2 ml TEOS solution and 23.2 ml ethanol was added dropwise to solution A at a rate of 0.4 ml / min and stirred at 1000 rpm for 12 h at room temperature; then the solution was filtered and washed with water three times, the product was dried completely in an oven at 60 °C and then calcined in air at 550 °C for 6 h in a muffle furnace to remove the CTAB template to obtain mesoporous SiO2 powder; (2) The mesoporous SiO2 powder was added to 100 ml of 0.5 mol / L NaOH solution and stirred at 80°C for 2 h to modify its surface with hydroxyl groups; then, the powder was filtered, washed with water three times, and dispersed in water at a ratio of 10 wt% to obtain water-dispersible hydroxyl-modified mesoporous SiO2 microspheres; (3) Prepare PDMS solution with a mass ratio of 10:1 between PDMS main agent and curing agent and mix well; (4) Centrifuge 2 ml of 10 wt% hydroxyl-modified mesoporous SiO2 microspheres to remove water, mix the centrifuged SiO2 microspheres with the PDMS solution in a mass ratio of 1:2, and stir evenly; then perform a vacuum operation to remove bubbles to obtain a PDMS@SiO2 mixed solution; (5) The obtained PDMS@SiO2 mixed solution was coated on a clean glass substrate by blade coating to form a 1 mm thick film, and then cured on a heating table at 40 °C for 12 h; (6) After the film is cooled naturally, it is peeled off the glass slide and placed in a PEI aqueous solution (8 mg mL -1 ) for 30 min for hydrophilic treatment, and finally the PDMS@SiO2 smart film was obtained.
[0041] The particle size of the polydisperse hydroxyl-modified mesoporous SiO2 microspheres synthesized in this example is 40-70 nm. The SEM image of the microspheres is shown in FIG. Figure 5 As shown in a. Figure 2 As shown in the figure, the prepared PDMS@SiO2 humidity-sensitive flexible smart film has an average transmittance of 70% and a haze of 29% at 400-800 nm in the dry state; after absorbing water, the PDMS@SiO2 flexible film has an average transmittance of 9% and a haze of 90% at 400-800 nm. Figure 1 As shown in a and b, the appearance of the film prepared in this example changes from a transparent film under dry conditions to a white film after absorbing water, which is a complete transformation. The PDMS@SiO2 flexible film prepared in this example can respond to humidity changes and achieve transmittance modulation and haze modulation of nearly 60%. Embodiment 2
[0042] (1) Synthesis of SiO2 microspheres by improved Stöber method: 0.26 g CTAB, 13.05 ml ethanol, 9 ml water and 0.8 ml ammonia water were mixed evenly to obtain solution A; a mixed solution of 1.5 ml TEOS and 13.05 ml ethanol was added dropwise to solution A at a rate of 0.2 ml / min and stirred at 1000 rpm for 2 h at room temperature; then the solution was filtered and washed with water three times, the product was dried completely in an oven at 60 °C and then calcined in a muffle furnace at 550 °C in air for 6 h to remove the CTAB template, thereby obtaining mesoporous SiO2 powder; (2) The obtained mesoporous SiO2 powder was added to 100 ml of 0.5 mol / L NaOH solution, stirred and reacted at 80°C for 2 h to modify its surface with hydroxyl groups; then filtered, washed with water three times, and dispersed in water at a ratio of 10 wt% to obtain water-dispersible hydroxyl-modified mesoporous SiO2 microspheres; (3) Prepare PDMS solution with a mass ratio of 10:1 between PDMS main agent and curing agent and mix well; (4) Centrifuge 2 ml of 10 wt% hydroxyl-modified mesoporous SiO2 microspheres to remove water, mix the centrifuged SiO2 microspheres with the PDMS solution in a mass ratio of 1:2, and stir evenly; then perform a vacuum operation to remove bubbles to obtain a PDMS@SiO2 mixed solution; (5) The obtained PDMS@SiO2 mixed solution was coated on a clean glass substrate by blade coating to form a 1 mm thick film, and then cured on a heating table at 40 °C for 12 h; (6) After the film is cooled naturally, it is peeled off the glass slide and immersed in a PEI aqueous solution for 30 min for hydrophilic treatment to obtain the PDMS@SiO2 smart film.
[0043] The particle size distribution of the polydisperse hydroxyl-modified mesoporous SiO2 microspheres synthesized in this example is 100-300 nm. The SEM image is as follows: Figure 5 As shown in b. Figure 3 As shown in the figure, the prepared PDMS@SiO2 humidity-sensitive flexible smart film has an average transmittance of 38% and a haze of 53% at 400-800 nm in the dry state; after absorbing water, the PDMS@SiO2 flexible film has an average transmittance of 67% and a haze of 19% at 400-800 nm. Figure 1 As shown in c and d, the appearance of the film changes from white in a dry state to transparent after absorbing water. The PDMS@SiO2 flexible film prepared in this example can respond to humidity changes and achieves a transmittance modulation of nearly 30% and a haze modulation of about 34%. Embodiment 3
[0044] (1) Synthesis of SiO2 microspheres by improved Stöber method: 0.26 g CTAB, 13.05 ml ethanol, 9 ml water and 0.8 ml ammonia water were mixed evenly to obtain solution A; a mixed solution of 1.5 ml TEOS and 13.05 ml ethanol was poured into solution A, and the mixture was reacted at 400 rpm for 2 min at room temperature and then stirred at 1000 rpm for 2 h; the mixture was then filtered and washed with water three times, the product was dried completely in an oven at 60 °C and then calcined in air at 550 °C for 6 h in a muffle furnace to remove the CTAB template, and mesoporous SiO2 powder was obtained; (2) The mesoporous SiO2 powder was added to 100 ml of 0.5 mol / L NaOH solution, and the mixture was stirred and reacted in a water bath at 80°C for 2 h to modify the surface of the powder with hydroxyl groups. The powder was then filtered, washed with water three times, and dispersed in water at a ratio of 10 wt% to obtain water-dispersible hydroxyl-modified mesoporous SiO2 microspheres. (3) Prepare PDMS solution with a mass ratio of 10:1 between PDMS main agent and curing agent and mix well; (4) Centrifuge 2 ml of 10 wt% hydroxyl-modified mesoporous SiO2 microspheres to remove water, mix the centrifuged SiO2 microspheres with the PDMS solution at a mass ratio of 1:9, and stir evenly; then vacuum the solution to remove bubbles to obtain a PDMS@SiO2 mixed solution; (5) The obtained PDMS@SiO2 mixed solution was coated on a clean glass substrate by blade coating to form a 1 mm thick film, and then cured on a heating table at 40 °C for 12 h; (6) After the film is cooled naturally, it is peeled off the glass slide and immersed in a PEI aqueous solution for 30 min for hydrophilic treatment to obtain the PDMS@SiO2 smart film.
[0045] The particle size of the monodisperse hydroxyl-modified mesoporous SiO2 microspheres synthesized in this example is D50 = 220 nm, and the SEM image is as follows: Figure 5 As shown in c, the particle size distribution is shown in Figure 6 .like Figure 4 As shown in the figure, the prepared PDMS@SiO2 humidity-sensitive flexible smart film has an obvious absorption peak near 550 nm in the dry state, and presents a green appearance due to the SiO2 photonic crystal characteristics; after absorbing water, the absorption peak of the PDMS@SiO2 flexible film disappears, and the transmittance of the full band of 400-800 nm is improved, presenting a colorless and transparent appearance. Figure 1 As shown in Figures e and f, the PDMS@SiO2 flexible film prepared in this example can respond to humidity changes and achieve a change in appearance from green to colorless. In addition, there is no color change between the films of Example 1 and Example 2. The particle size of Example 1 is small, and no diffraction is generated in the visible light band, showing changes in haze and transmittance caused by scattering; the SiO2 of Example 2 cannot form a short-range ordered arrangement and does not produce corresponding structural colors.
[0046] Comparative Example 1 (1) Prepare PDMS solution with a mass ratio of 10:1 between PDMS main agent and curing agent and mix well; (2) Mixing the mesoporous SiO2 powder (prepared in Example 1) and the PDMS solution in a mass ratio of 1:2 and stirring evenly; then performing a vacuum operation to remove bubbles to obtain a PDMS / SiO2 mixed solution; (3) The obtained PDMS / SiO2 mixed solution was coated on a clean glass substrate by blade coating to form a 1 mm thick film, and then cured on a heating table at 40 °C for 12 h; (4) After the film is cooled naturally, it is peeled off the glass slide and placed in a PEI aqueous solution (8 mg mL -1 ) for 30 min for hydrophilic treatment, and finally the PDMS / SiO2 smart film was obtained.
[0047] The particle size of the above-mentioned multi-dispersed mesoporous SiO2 microspheres is 40 to 70 nm. Figure 7 As shown, the prepared PDMS@SiO2 humidity-sensitive flexible smart film has an average transmittance of 49% and a haze of 52% at 400-800 nm in the dry state; after absorbing water, the PDMS@SiO2 flexible film has an average transmittance of 40% and a haze of 59% at 400-800 nm, and the spectrum changes by less than 10% before and after water absorption; the film appears to be a translucent film with almost no change before and after water absorption. Embodiment 4
[0048] Refer to Example 1, except that the immersion in the PEI aqueous solution is omitted.
[0049] like Figure 8As shown, the prepared PDMS@SiO2 humidity-sensitive flexible smart film has an average transmittance of 68% and a haze of 29% at 400-800 nm in a dry state; after absorbing water, the PDMS@SiO2 flexible film has an average transmittance of 22% and a haze of 77% at 400-800 nm. Compared with Example 1, PEI immersion was not used in this example. In a dry state, the average transmittance and haze of the film of this example are basically the same as those of Example 1, but after absorbing water, the average transmittance is 13% higher than that of Example 1, and the spectral modulation amplitude is reduced to 46%. Fig. 9 As shown, the time-resolved transmittance of Example 1 and Example 4 at a wavelength of 600 nm was characterized by a UV-visible spectrometer. The results showed that from the dry state, Example 1 absorbed water and the transmittance decreased much faster than Example 4. After 300 s, the water absorption of Example 1 was close to saturation, and the transmittance reached 11%, while the transmittance of Example 4 only reached 42%. The water absorption rate of the microspheres in Example 4 without PEI soaking was much lower than that of Example 1 after PEI soaking. Embodiment 5
[0050] Referring to Example 3, the mixing of SiO2 microspheres and PDMS solution in a mass ratio of 1:1 in step (4) is changed to mixing of SiO2 microspheres and PDMS solution in a mass ratio of 1:1, and the rest remain the same, and finally a PDMS@SiO2 smart film is obtained.
[0051] The prepared PDMS@SiO2 humidity-sensitive flexible smart film has a less obvious absorption peak than the film in Example 3 in the dry state, and its appearance shows a lighter green color, close to white. Figure 1 As shown in g and h, the proportion of microspheres is high, and the film transmittance is significantly reduced. Compared with Example 3, the average transmittance is reduced by 30% under both water absorption conditions and dry conditions. Fig.10 The transmittance and haze spectra of the above film before and after water absorption.
[0052] In existing reports, humidity-responsive films rely on materials such as hydrogels, liquid crystals, and cross-linked films to achieve color change in response to moisture. Compared with these humidity-responsive films, the present invention only relies on the change in refractive index after the microspheres absorb water to produce optical response. The present invention has the following advantages: relying on the long-range disordered and short-range ordered distribution characteristics of the microspheres, the present invention can produce angle-independent structural colors; by adjusting the size and particle size distribution of the microspheres, the present invention can effectively change the response wavelength to adapt to different application scenarios; the present invention can still maintain complete spectral response capabilities after repeated water absorption and dehydration.
[0053] The purpose of the present invention is to prepare a stimuli-responsive hydrochromic flexible smart film based on polymer@mesoporous microspheres. As a preferred example, a certain proportion of hydroxyl-modified mesoporous SiO2 microspheres are added to the PDMS main agent curing agent liquid, mixed evenly, and coated on a clean glass sheet by spin coating, scraping, printing and spraying, and then peeled off after heating and curing to obtain a smart film whose optical properties are self-modulated with humidity changes.
[0054] The present invention prepares a humidity-sensitive PDMS@SiO2 flexible smart film. According to the different sizes of SiO2 microspheres used, the flexible smart film can make different optical responses to different humidity conditions.
[0055] The above is only a preferred implementation method of the present invention and does not limit the scope of application of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and adjustments can be made without exceeding the technical principles of the present invention, and these improvements and adjustments should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a hydrochromic flexible smart film, comprising the following steps: The polymer precursor is mixed with the hydrophilically modified mesoporous nanospheres and then cured into a film to obtain a hydrochromic flexible smart film.
2. The method for preparing the hydrochromic flexible smart film according to claim 1, characterized in that: After solidification into a film, the obtained film is subjected to hydrophilic treatment to obtain a hydrochromic flexible smart film.
3. The method for preparing the hydrochromic flexible smart film according to claim 2, characterized in that: The hydrophilic treatment includes the following steps: immersing the film in a polyethyleneimine aqueous solution to complete the hydrophilic treatment.
4. The method for preparing the hydrochromic flexible smart film according to claim 1, characterized in that: The hydrophilic modification is modification with a hydrophilic group or a hydrophilic polymer.
5. The method for preparing the hydrochromic flexible smart film according to claim 4, characterized in that: The hydrophilic modification includes one or more modifications of hydroxyl, secondary amino, polyoxyethylene methacrylate, and polyethylene glycol.
6. The method for preparing the hydrochromic flexible smart film according to claim 1, characterized in that: The mesoporous nano-microspheres include one or more of silica microspheres and titanium dioxide microspheres.
7. The method for preparing the hydrochromic flexible smart film according to claim 1, characterized in that: The mesoporous nanospheres are polydisperse mesoporous nanospheres or monodisperse mesoporous nanospheres.
8. The method for preparing the hydrochromic flexible smart film according to claim 1, characterized in that: The polymer includes one or more of polydimethylsiloxane, polyethylene terephthalate, and polyimide. 9 . The hydrochromic flexible smart film prepared according to the method for preparing the hydrochromic flexible smart film according to claim 1 .
10. Use of the hydrochromic flexible smart film according to claim 9 in preparing humidity responsive materials, or in preparing optical responsive materials, or in preparing materials that respond to changes in transmittance, haze or appearance.
Citation Information
Cited By
Thermochromic silica gel composite material with slow color fading as well as preparation method and application of thermochromic silica gel composite material
CN119490752A
A slow-fading thermochromic silica composite material and its preparation method and application
CN119490752B